PROGRAM PENINGKATAN KEMAMPUAN ORANG TUA DAN GURU DALAM MEMBANTU KEMANDIRIAN SHOLAT ANAK TUNAGRAHITA RINGAN - Tarsono Tarsono (Psympathic : Jurnal Ilmiah Psikologi, 2013)
This research aims to help mentally disabled students to pray independently by giving suggestion to parrents and teachers. Qualitative approach using interview, observation and documentation are used to collect data. Result shows that some mentally disabled students have not been able to have five times praying with correct reading prayer and movement. Parents can ask to pray together, invite teacher and provide some media. Meanwhile, teacher could make schedule for praying together and make a realia. Constraints faced are lack of mentally disabled knowledge, no appropriate realia and lack of attention  toward mentally disabled students.